2022
DOI: 10.1002/aps3.11461
|View full text |Cite
|
Sign up to set email alerts
|

Mycobiome detection from a single subterranean gametophyte using metabarcoding techniques

Abstract: Premise Several ferns and lycophytes produce subterranean gametophytes, including the Ophioglossaceae, Psilotaceae, and some members of the Schizaeaceae, Gleicheniaceae, and Lycopodiaceae. Despite the surge in plant‐microbiome research, which has been particularly boosted by high‐throughput sequencing techniques, the microbiomes of these inconspicuous fern gametophytes have rarely been examined. The subterranean gametophytes are peculiar due to their achlorophyllous nature, which makes them rely o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Discrepancies in the ability of the two markers to detect AMF communities have been previously reported (Öpik et al, 2014 ; Lekberg et al, 2018 ), but the information is very incomplete in the case of ferns and lycophytes. Perez‐Lamarque et al ( 2022 ) focused on the complementary capacities of the 18S and ITS protocols to detect the whole fungal community, whereas Chen et al ( 2022 ) only indicated that distinct primer sets captured differences in fungal taxonomic abundance on a single subterranean gametophyte of Ophioderma pendulum L. Indeed, the NS31/AML2 primer set has been reported as highly effective to amplify a wider diversity of AMF taxa than other 18S‐specific and ITS‐specific pairs (Öpik et al, 2010 ; Tedersoo et al, 2022 ). However, fundamental differences in the reference databases used could also have influenced this outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancies in the ability of the two markers to detect AMF communities have been previously reported (Öpik et al, 2014 ; Lekberg et al, 2018 ), but the information is very incomplete in the case of ferns and lycophytes. Perez‐Lamarque et al ( 2022 ) focused on the complementary capacities of the 18S and ITS protocols to detect the whole fungal community, whereas Chen et al ( 2022 ) only indicated that distinct primer sets captured differences in fungal taxonomic abundance on a single subterranean gametophyte of Ophioderma pendulum L. Indeed, the NS31/AML2 primer set has been reported as highly effective to amplify a wider diversity of AMF taxa than other 18S‐specific and ITS‐specific pairs (Öpik et al, 2010 ; Tedersoo et al, 2022 ). However, fundamental differences in the reference databases used could also have influenced this outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these angiosperm parasites not having been reported to directly host on a fern, these angiosperms are possible to contact with ferns indirectly via mycorrhizal fungi ( Brundrett, 2002 ; Heide-Jørgensen, 2010 ; de Vega et al., 2011 ). Such a scenario is plausible especially for Ophioglossaceae ferns because they are always symbiotic with mycorrhizal fungi in their life history that starts from a mycoheterotrophic gametophyte generation to a sporophyte generation relying on mycorrhizae ( Lang, 1902 ; Winther and Friedman, 2007 ; Whittier, 2015 ; Chen et al., 2022 ). In addition, two mitochondrial HGTs in Mankyua were found to originate from other Ophioglossaceae ferns, most likely Sceptridium in subfamily Botrychioideae; and the others were from non-Ophioglossaceae ferns ( Table 2 ; Figure S4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this phylogenetic study sets the stage for future work delving into the unique biological features of Schizaeaceae and in Schizaeales, such as Mesozoic biogeography ( Skog, 2001 ), epiphytism on tree ferns ( Amoroso et al, 2020 ), leaf simplification and lamina reformation ( Vasco et al, 2013 ), biosynthesis of silica bodies ( Ribeiro et al, 2007 ; Tzu-Tong Kao personal communications), and recruitment of symbiotic microbiome (e.g., Chen et al, 2022 ). Lastly, the pheromone-mediated (i.e., antheridiogen) mating system has been well-studied in the other two Schizaeales families ( Yamane, 1991 , 1998 ; Tanaka et al, 2014 ) but not yet for Schizaeaceae.…”
Section: Discussionmentioning
confidence: 99%